Effects of external limb compression and/or low-load resistance exercise on post-activation performance enhancement during countermovement jumps - Zheng, Z.; Wang, Y.; Wei, H.; Zhang, J.; Yan, B.; Girard, O. (European Journal of Sport Science, 2024)
The effects of low-load resistance exercise combined with external limb compression (ELC) to augment post-activation performance enhancement during countermovement jumps have yet to be examined. We assessed the separate and combined effects of ELC and sets of low-load (back squats) resistance exercise (both compared with controls) during conditioning routines, and determine their subsequent neuromechanical consequences during countermovement jumps. On separate days, twenty strength-trained men completed a familiarization session followed by four experimental trials in a randomized design that included one of the following conditioning routines: passive rest (Control [CON], no occlusion/standing), exercise (sets of low-intensity resistance exercise [RE] with 30% 1RM, no occlusion/exercise), ELC ([ELC] at 80% of the individual arterial occlusion pressure, occlusion/standing), and combined ELC and exercise ([ELC + RE], occlusion/exercise). Countermovement jump performance (jump height, relative peak power output, vertical impulse, and rate of force development) was assessed at baseline, immediately after, and at the third, sixth, ninth and twelfth minute following each conditioning routine. Compared to baseline, jump height, relative peak power output and vertical impulse values were lower at 0 min for [RE] (-3.5%-8.2%; p = 0.014) and higher at +3 min for [ELC] (+2.0%-3.8%; p = 0.013). Regarding [ELC + RE], values for these three variables were lower at 0 min (-4.8%-8.0%; p < 0.001) but higher at +12 min (+2.9%-5.5%; p < 0.001) versus baseline. In strength-trained men, using ELC either alone (while standing) or combined with low-load resistance exercise sets (during back squats) can be a useful way to improve CMJ mechanics. However, the duration and magnitude of post-activation potentiation performance benefits varied depending on the type of ELC protocol used.